ZZ Piscis Austrinus (ZZ PsA): a bright red nova progenitor and the instability mass ratio of contact binary stars. Issue 1 (26th November 2020) - Wadhwa, Surjit S; De Horta, Ain; Filipović, Miroslav D; Tothill, N F H; Arbutina, Bojan; Petrović, Jelena; Djurašević, Gojko
ABSTRACT: ZZ Piscis Austrinus (ZZ PsA) is a neglected bright southern contact binary system with maximum V magnitude of 9.26. We present the first multiband photometric analysis and find the system to be in deep contact (>95 per cent) with an extremely low mass ratio of 0.078. The primary has a mass of 1.213 M⊙ in keeping with its reported spectral class of F6. In order to determine if ZZ PsA is a merger candidate, we outline the current status regarding the instability mass ratio and develop new relationship linking the mass of the primary to the instability mass ratio of the system and the degree of contact. We find that ZZ PsA along with two other examples from the literature to be merger candidates while an additional three require further observations to be confirmed as potential merger candidates.